2019
DOI: 10.4314/jasem.v23i6.12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating rule breaking behavior in a Nigerian protected forest reserve area

Abstract: This paper investigated the rule breaking conduct in a Nigerian protected forest reserve area in order to exploit natural resources using Randomized Response Technique (RRT) for data collection. Evident from this study show a higher proportion of the residents surrounding Oba Hills Forest Reserve, Nigeria illegally poach, encroach to farm, extract timber, gather firewood and graze their domestic animals in the conservation area. With the high level of noncompliance to the conservation rules in this study, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Old Oyo National Park, Nigeria's fourth largest, is situated in the southwestern part of the country (Figure 1), with annual rainfall ranging from 1100 to 1500 mm and altitude ranging from 330 to 508 m. Generally, the vegetation is southern Guinea savannah, categorised into three sub‐habitats: mixed open savannah woodland in the central part, dense woodland and forest outliers in the southern part, and outcrop vegetation in the north‐eastern part. The park was reported to have 25 species of terrestrial mammals whose bodyweight was >1 kg (Akinsorotan, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Old Oyo National Park, Nigeria's fourth largest, is situated in the southwestern part of the country (Figure 1), with annual rainfall ranging from 1100 to 1500 mm and altitude ranging from 330 to 508 m. Generally, the vegetation is southern Guinea savannah, categorised into three sub‐habitats: mixed open savannah woodland in the central part, dense woodland and forest outliers in the southern part, and outcrop vegetation in the north‐eastern part. The park was reported to have 25 species of terrestrial mammals whose bodyweight was >1 kg (Akinsorotan, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Information on the demography and conservation status of Nigeria's terrestrial mammals is scarce (Convention on Biological Diversity, 2015). Our study area, as a single section heavily surrounded by human settlements, historically was home to top predators and megafaunas like elephant and buffalo (Akinsorotan, 2017), and migration of animals is very unlikely. The need for accurate data on terrestrial large mammal populations and conservation status is essential for updating sustainable management strategies and answering the following research questions: (1) what is the population size of the terrestrial large mammal species in study area?…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in Uganda, an ecological survey of the Bwindi Impenetrable NP showed that rule-breaking was reported to be a routine activity in this terrestrial ecosystem (Butynski, 1984), which is home to Africa's iconic mountain gorillas (Gorilla beringei beringei) (Wilson and Primack, 2019). Lastly, Akinsorotan et al (2019) evaluated rule-breaking behaviour in the protected Oba Hills Forest Reserve, Nigeria, and found nearby inhabitants to exhibit a high degree of non-compliance with rules governing this particular reserve.…”
Section: Introductionmentioning
confidence: 99%